Hikmah Larangan Ihtikar Mekanisme Pasar Domestik dalam Ekonomi Islam - Luluk Illiyah; Irdlon Sahil (Prodi Ekonomi Syariah STAI Syaichona Moh. Cholil Bangkalan, 2023)
Some economic activities that can, in practice, benefit one party and harm another from religious values, such as usury, tadlis gambling in buying and selling, and the hoarding of goods or what is commonly known as Ihtikar. In fact, in economic activity, a sense of transcendence is very necessary and required. If this feeling and awareness are not found, then everyone will justify all means without caring about the consequences of their behavior and they will even argue that if this is not the case then the economy in a circle will not run quickly and optimally. The definition of Ihtikar is an economic practice that is carried out by hoarding certain goods which have the aim of obtaining the maximum profit without caring about how distressed others are when they need it. In this case, Islam provides a separate prohibition to maintain the survival of mankind on this earth and also so that the economy of a country can move forward, normal and full of equality and justice, of course